Polyimide varnish for high-functional conductor coating, and polyimide coating prepared therefrom
The polyimide varnish formulation with boron nitride, nanosilica, and dispersant additives addresses the challenge of enhancing voltage durability, thermal conductivity, and adhesive strength, improving motor performance and process efficiency.
Patent Information
- Application Number
- JP2024105682
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-30
- Filing Date
- 2024-06-28
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2044-06-28
AI Technical Summary
Existing polyimide resins face challenges in achieving simultaneous improvements in voltage durability, adhesive strength, thermal conductivity, and friction coefficient, often leading to deteriorated physical properties when attempting to enhance one characteristic.
A polyimide varnish formulation containing diamine and dianhydride monomers, boron nitride as a first additive, nanosilica as a second additive, and a dispersant, along with a silane coupling agent, to enhance thermal conductivity, adhesive strength, and reduce friction.
The formulation results in improved voltage durability, thermal conductivity, and adhesive strength, with reduced friction, enhancing motor durability and process efficiency in electric vehicle windings.
Smart Images

Figure 2025010055000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyimide varnish and a polyimide coating produced therefrom, in particular to a polyimide varnish and a polyimide coating produced therefrom that have improved voltage durability, adhesion, and thermal conductivity after curing, and an improved coefficient of friction. [Background technology]
[0002] The insulating layer (insulating coating) that covers the conductor is required to have excellent insulation properties, adhesion to the conductor, heat resistance, mechanical strength, etc. Examples of resins that can be used for the insulating layer include polyimide resin, polyamide-imide resin, polyester-imide resin, etc. Among these, polyimide resin in particular is a material that has excellent heat resistance and insulation properties, and has excellent properties for use as a coating material for conductors.
[0003] Polyimide resin is a highly heat-resistant resin produced by solution polymerization of aromatic dianhydride and aromatic diamine or aromatic diisocyanate to produce a polyamic acid derivative, followed by ring-closing dehydration at high temperature and imidization. For example, a method of forming an insulating coating using such a polyimide resin can be used in which a polyimide varnish, which is a precursor of the polyimide resin, is applied or coated around an electric wire made of a conductor, and then the polyimide varnish is imidized in a curing furnace capable of performing heat treatment at a predetermined temperature.
[0004] In the method of forming such an insulating coating, the physical properties, productivity, and production costs of the insulating coating may differ depending on conditions such as the temperature of the curing oven, the number of coatings of polyimide varnish, the coating speed, etc. That is, forming an insulating coating at a high temperature may be advantageous for producing an insulating coating having excellent physical properties, and the fewer the number of coatings or the faster the coating speed, the more improved the productivity.
[0005] However, if the temperature of the curing oven is too high, defects may occur on the surface of the insulating coating or the polyimide resin may be carbonized, and if the number of coatings is too small or the coating speed is too fast, the physical properties of the polyimide coating may be reduced. In addition, despite their excellent physical properties, general polyimide resins do not have good adhesive strength with conductors, so that a problem of poor appearance may occur when forming an insulating coating.
[0006] As described above, there are various drawbacks to improving the properties required for polyimide varnish and polyimide resins produced therefrom. In particular, improving one property generally results in a decrease in other properties. Therefore, simultaneously satisfying various properties is a challenge that continues to be researched in related technical fields.
[0007] Therefore, there is a strong need for a polyimide varnish for conductor coating which is excellent in the above-mentioned productivity and process efficiency, simultaneously satisfies the heat resistance, insulating properties and mechanical properties of polyimide, and has excellent adhesive strength to a conductor. Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a polyimide varnish which, after curing, has improved voltage durability, adhesive strength, and thermal conductivity, and an improved coefficient of friction, and a polyimide coating produced therefrom.
[0009] Another object of the present invention is to provide a polyimide varnish for a highly functional conductor coating to be used for windings of electric vehicles (EVs), and a polyimide coated article produced using the same. [Means for solving the problem]
[0010] Since the present invention can be modified in various ways and can have various embodiments, a specific embodiment will be illustrated and described in detail. However, it should be understood that the present invention is not limited to the specific embodiment, and includes all modifications, equivalents, or alternatives included in the spirit and technical scope of the present invention.
[0011] The terms used in this application are merely used to describe certain embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this application, the terms "include" or "have" are used to specify the presence of a feature, number, step, operation, component, part, or combination thereof described in the specification, and should be understood not to preclude the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0012] When an amount, concentration, or other value or parameter is given herein as a range, a preferred range or a list of upper preferred values and lower preferred values, that should be understood to specifically disclose all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether a range is otherwise disclosed.
[0013] When a range of numerical values is recited herein, unless otherwise stated, the range includes its endpoints and limits within the range, and the scope of the invention is not intended to be limited to the specific values recited when defining the range.
[0014] As used herein, "dianhydrides" is intended to include precursors or derivatives thereof, but may also be referred to as "dianhydride acids," "dianhydrides," or "acid dianhydrides." These may not technically be dianhydrides, but may nevertheless react with diamines to form polyamic acids, which may also be converted to polyimides.
[0015] As used herein, "diamine" is intended to include precursors or derivatives thereof which may not technically be diamines, but which nevertheless react with dianhydride acids to form polyamic acids, which can also be converted to polyimides.
[0016] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with the meaning they have in the context of the relevant art, and should not be interpreted in an ideal or overly formal sense unless expressly defined in this application. Specific contents for implementing the above invention are described as follows.
[0017] The present invention relates to a polyimide varnish for highly functional conductor coating and a polyimide coating produced therefrom.
[0018] Polyimide Varnish The present invention provides a polyimide varnish comprising a polyamic acid solution containing a diamine monomer and a dianhydride monomer as polymerized units, a first additive containing boron nitride, a second additive containing nanosilica, and a dispersant.
[0019] Polyamic Acid Solution The diamine monomer is 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP), metaphenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl) ethyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diamino diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-amino phenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylsulfide)benzene, 1,3-bis(4-aminophenylsulfide)benzene, 1,4-bis(4-aminophenylsulfide)benzene, 1,3 -Bis(3-aminophenylsulfone)benzene, 1,3-bis(4-aminophenylsulfone)benzene, 1,4-bis(4-aminophenylsulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4- 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1 ,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, preferably, one or more selected from the group consisting of 1,4-diaminobenzene (PPD) and 4,4'-diaminodiphenyl ether (ODA), more preferably, 1,4-diaminobenzene (PPD) and 4,It may contain 4'-diaminodiphenyl ether (ODA).
[0020] The dianhydride monomer is selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)sulfide dianhydride, and 2,2-bis(3,4-dicarboxyphenyl)sulfide dianhydride. (3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylene bis(trimeric monoester acid anhydride), p-biphenylene bis(trimeric monoester Terphenyl anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[( The dianhydride may include one or more selected from the group consisting of 3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride, and preferably may include pyromellitic dianhydride (PMDA).
[0021] In the present invention, pyromellitic dianhydride (PMDA) may be contained in a ratio of 50 mol% or more of the total dianhydride monomers, specifically, 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.
[0022] In addition, 4,4'-diaminodiphenyl ether (ODA) may be contained in a ratio of 0 to 100 mol% of the total diamine monomers, specifically, 50 to 95 mol%, 60 to 90 mol%, 65 to 85 mol%, 70 to 80 mol%, or 73 to 77 mol%. When 4,4'-diaminodiphenyl ether (ODA) is contained in a ratio of 0 mol%, 1,4-diaminobenzene (PPD) may be contained in a ratio of 100 mol%.
[0023] In addition, 1,4-diaminobenzene (PPD) may be contained in a ratio of 0 to 100 mol% of the total diamine monomers, specifically, 5 to 45 mol%, 10 to 40 mol%, 15 to 35 mol%, 20 to 30 mol%, or 23 to 27 mol%. When 1,4-diaminobenzene (PPD) is contained in a ratio of 0 mol%, 4,4'-diaminodiphenyl ether (ODA) may be contained in a ratio of 100 mol%.
[0024] The polyamic acid solution may contain the diamine monomer in an amount of 90 to 110 mol %, preferably 95 to 105 mol %, more preferably 98 to 102 mol %, and further preferably 99 to 101 mol %.
[0025] The polyamic acid solution may contain the dianhydride monomer in an amount of 90 to 110 mol %, preferably 95 to 105 mol %, more preferably 98 to 102 mol %, and even more preferably 100 mol %.
[0026] The polyamic acid solution may have 95 to 105 mol% of the dianhydride monomer relative to 100 mol% of the diamine monomer. For example, the lower limit may be 95.5 mol% or more, 96 mol% or more, 96.5 mol% or more, 97 mol% or more, 97.5 mol% or more, 98 mol% or more, 98.5 mol% or more, 99 mol% or more, or 99.5 mol% or more, and the upper limit may be 105 mol% or less, 104 mol% or less, 103 mol% or less, 102 mol% or less, 101 mol% or less, or 100 mol% or less.
[0027] The polyamic acid solution may contain the dianhydride monomer and the diamine monomer in a molar ratio of 6:4 to 4:6.
[0028] The polyamic acid solution may further include an organic solvent.
[0029] The organic solvent may include one or more selected from the group consisting of N,N'-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), dimethylsulfoxide (DMSO), diethylacetamide (DEAc), N-ethyl-2-pyrrolidone (NEP), N,N'-diethylformamide (DEF), dimethylpropanamide (DMPA), and γ-butyrolactone (GBL). Preferably, N,N'-dimethylacetamide (DMAc) can be used.
[0030] First Additive The polyimide varnish of the present invention may include a first additive comprising boron nitride.
[0031] The first additive may be contained in an amount of 1 to 40% by weight, preferably 2.5 to 20% by weight, more preferably 3 to 15% by weight, and further preferably 4 to 12% by weight, based on the solid content weight of the polyimide varnish.
[0032] If the content of the first additive exceeds 40 wt%, the mechanical properties of the polyimide coating may be deteriorated and the amount of additive is too large to uniformly disperse the polyimide coating, which is not preferred. On the other hand, if the content of the first additive is less than 1 wt%, the heat dissipation property is not improved, which is not preferred.
[0033] The particle size (D90) of the first additive may be 1 to 20 μm. For example, the lower limit may be 1.5 μm, 1.7 μm, 1.9 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, or 3.5 μm or more, and the upper limit may be 9.5 μm, 9.0 μm, 8.5 μm, 8.0 μm, 7.5 μm, 7.0 μm, 6.5 μm, 6.0 μm, 5.8 μm, 5.7 μm, or 5.5 μm or less.
[0034] The boron nitride may be one or more selected from the group consisting of cubic boron nitride (cBN), amorphous boron nitride (aBN) and hexagonal boron nitride (hBN), and is preferably hexagonal boron nitride (hBN).
[0035] Second Additive The polyimide varnish of the present invention may include a second additive comprising nanosilica.
[0036] The second additive may be included in an amount of 0.01 to 60% by weight based on the solid content weight of the polyimide varnish. For example, the lower limit of the content of the second additive may be 0.03% by weight or more, 0.05% by weight or more, 0.07% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.4% by weight or more, or 0.5% by weight or more, and the upper limit may be 50% by weight or less, 30% by weight or less, 10% by weight or less, 7% by weight or less, 3% by weight or less, 1.5% by weight or less, 1.2% by weight or less, or 1% by weight or less.
[0037] If the content of the second additive exceeds 60 wt %, the mechanical properties of the polyimide coating may be deteriorated, which is not preferable, whereas if the content is less than 0.01 wt %, the effect of improving voltage durability is not observed, which is not preferable.
[0038] The average particle size of the second additive may be 1 to 200 nm, specifically, for example, 5 to 150 nm, 5 to 100 nm, 5 to 70 nm, 10 to 50 nm, or 10 to 30 nm. The average particle size may be measured by equipment such as BET, SEM, and zeta potential.
[0039] Dispersants The polyimide varnish of the present invention may contain a dispersant to improve the dispersibility of the first additive.
[0040] The dispersant may include at least one selected from the group consisting of polyethylene dispersants, polyester dispersants, polycarboxylate dispersants, unsaturated polyamide dispersants, polycarboxylate dispersants, polyalkyl polycarboxylate dispersants, polyacrylic dispersants, polyethyleneimine dispersants, and polyurethane dispersants, and preferably, polyurethane dispersants can be used. The strong polarity of the polyurethane dispersant can improve the dispersing power of boron nitride.
[0041] The polyurethane-based dispersant may be a polyurethane polymer as a dispersant having an amine value and / or an acid value, and may be a polymer containing a urethane bond in the structure as a high dispersion dispersant having only an amine value.
[0042] The dispersant used may have an acid value in the range of 10 to 200 mgKOH / g or an amine value in the range of 5 to 200 mgKOH / g, but is not limited thereto.
[0043] In one embodiment, the acid value of the dispersant may be about 20 mgKOH / g or more, 30 mgKOH / g or more, 40 mgKOH / g or more, 50 mgKOH / g or more, 60 mgKOH / g or more, 70 mgKOH / g or more, 80 mgKOH / g or more, or 90 mgKOH / g or more, or about 190 mgKOH / g or less, 180 mgKOH / g or less, 170 mgKOH / g or less, 160 mgKOH / g or less, 150 mgKOH / g or less, 140 mgKOH / g or less, 130 mgKOH / g or less, 120 mgKOH / g or less, 110 mgKOH / g or less, or 100 mgKOH / g or less. Here, the acid value means a value obtained by titrating the acid group (-COOH) possessed by the dispersant with KOH and dividing it by the KOH consumption (a value expressed in mg of the consumption of KOH titrated per 1 g of dispersant).
[0044] In one embodiment, the amine number of the dispersant may be about 10 mgKOH / g or more, about 15 mgKOH / g or more, about 20 mgKOH / g or more, 30 mgKOH / g or more, 40 mgKOH / g or more, 50 mgKOH / g or more, 60 mgKOH / g or more, 70 mgKOH / g or more, 80 mgKOH / g or more, or 90 mgKOH / g or more, or about 190 mgKOH / g or less, 180 mgKOH / g or less, 170 mgKOH / g or less, 160 mgKOH / g or less, 150 mgKOH / g or less, 140 mgKOH / g or less, 130 mgKOH / g or less, 120 mgKOH / g or less, 110 mgKOH / g or less, or 100 mgKOH / g or less. Here, the amine value means a value obtained by titrating the amino groups (-NH2, -NHR or -NR2) contained in the dispersant with KOH and dividing the result by the amount of KOH consumed (a value expressed in mg of the amount of KOH consumed titrated per 1 g of dispersant).
[0045] The dispersant may have a specific gravity of 0.5 to 1.5 g / ml at 20° C., and for example, the lower limit may be 0.6 g / ml, 0.7 g / ml, 0.8 g / ml, 0.9 g / ml, or 1.00 g / ml or more, and the upper limit may be 1.4 g / ml, 1.3 g / ml, 1.2 g / ml, 1.1 g / ml, 1.07 g / ml, or 1.05 g / ml or less.
[0046] The dispersant may be contained in an amount of 1 to 25% by weight, preferably 2.5 to 20% by weight, more preferably 3 to 15% by weight, even more preferably 3.3 to 10% by weight, and even more preferably 3.5 to 6.5% by weight, based on the weight of the first additive.
[0047] If the content of the dispersant is less than 1% by weight, it is not preferable because it does not improve the dispersibility of the first additive, and if the content of the dispersant is more than 25% by weight, it is not preferable because the thermal stability is reduced.
[0048] Polyimide varnish and its cured product The polyimide varnish may further include a silane coupling agent. The silane coupling agent may modify the surface of one or more of the first additive and the second additive. The surface is modified by the silane coupling agent to prevent the additive from agglomerating in the polyimide varnish, and the functional group of the silane coupling agent enhances the interaction with the solid content (polyamic acid), thereby improving dispersibility and miscibility.
[0049] The silane coupling agent may include at least one selected from the group consisting of epoxy silanes, alkyloxy silanes, amino silanes, methacryloxy silanes, isocyanate silanes, and fluorine silanes, and preferably includes an epoxy silane.
[0050] The epoxy silane system may include one or more selected from the group consisting of (3-glycidoxypropyl)trimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, (3-glycidoxypropyl)methyldimethoxysilane, (3-glycidoxypropyl)methyldiethoxysilane, and (3-glycidoxypropyl)triethoxysilane, and preferably includes (3-glycidoxypropyl)trimethoxysilane, and more preferably, among (3-glycidoxypropyl)trimethoxysilane products, OFS-6040 may be used.
[0051] The content of the silane coupling agent in the polyimide varnish may be 0.01 to 1% by weight, preferably 0.1 to 0.9% by weight, more preferably 0.3 to 0.7% by weight, and even more preferably 0.4 to 0.6% by weight.
[0052] The solid content of the polyimide varnish may be 5 to 40 wt%, preferably 10 to 38 wt%, and more preferably 12 to 35 wt%. If the solid content of the polyimide varnish exceeds the above range, the viscosity increases, which is undesirable as it is difficult to use the polyimide varnish as a coating material thereafter, and if the solid content is below the above range, a large amount of solvent needs to be removed during the curing process, which may cause problems such as increased manufacturing costs and process time.
[0053] The polyimide varnish according to the present invention may be cured into a film, and the thickness of the cured product may be appropriately selected in consideration of the intended use, the environment in which it is used, its physical properties, and the like.
[0054] In one embodiment, the polyimide varnish according to the present invention can have a thickness after curing of 20 to 40 μm. For example, the lower limit can be 21 μm or more, 22 μm or more, 23 μm or more, or 24 μm or more, and the upper limit can be 35 μm or less, 30 μm or less, 29 μm or less, 28 μm or less, or 27 μm or less.
[0055] In one embodiment, the polyimide varnish according to the present invention may have a coefficient of thermal expansion (CTE) after curing of 20 to 30 ppm / ° C., preferably 23 to 27 ppm / ° C., and more preferably 24 to 26 ppm / ° C. The coefficient of thermal expansion was measured by a TMA device (Q400) manufactured by TA Corporation, as a gradient in the range of 100 to 250° C. when the temperature was increased from room temperature to 350° C. at a rate of 10° C. / min.
[0056] In one embodiment, the polyimide varnish according to the present invention may have a thermal conductivity after curing of 0.2 to 0.8 W / mK, preferably 0.23 to 0.5 W / mK, and more preferably 0.25 to 0.45 W / mK. The thermal conductivity was calculated by measuring the thermal diffusivity in the thickness direction (through-plane) of a cured product obtained by curing the polyimide varnish under N2 nitrogen gas conditions using a thermal conductivity meter (LFA, manufactured by NETZSCH, LFA467), and multiplying the measured thermal diffusivity by the density (weight / volume) and specific heat (measured specific heat using DSC).
[0057] In one embodiment, the polyimide varnish according to the present invention has a voltage durability of 400 minutes or more, which is the time that an insulating material can withstand a predetermined voltage according to IEC-60851-5 after curing, and the voltage durability may be measured on the polyimide (thickness: 26±0.5 μm) under conditions of AC 1.5 kV, frequency 60 Hz, and upper limit of leakage current 5 mA. Specifically, the voltage durability may be 410 minutes or more, 415 minutes or more, 420 minutes or more, 425 minutes or more, or 430 minutes or more. The voltage durability is measured by fixing a polyimide varnish cured product in the form of a film to a jig, applying a predetermined voltage, and measuring the time when a leakage current of 5 mA or more flows using a withstand voltage meter (TSURUGA, 8526).
[0058] In one embodiment, the polyimide varnish according to the present invention may have a coefficient of friction (PI-PI) between polyimide varnish cured products after curing of 0.38 or less, and preferably 0.35 or less. The coefficient of friction was measured by a friction coefficient measuring device (QM110CF, manufactured by QMESYS) under conditions of a load of 200 gf and a speed of 2.5 mm / s, in which one of the polyimide cured products in the form of a film is fixed to a weight and pulled at a constant speed on another polyimide cured product in the form of a film.
[0059] In one embodiment, the polyimide varnish according to the present invention may have a friction coefficient (PI-SUS) between the cured polyimide varnish and the stainless steel substrate after curing of 0.35 or less, and preferably 0.32 or less. The friction coefficient was measured by a friction coefficient measuring device (QM110CF, manufactured by QMESYS) under conditions of a load of 200 gf and a speed of 2.5 mm / s, in which a polyimide varnish cured film is fixed to a weight and pulled at a constant speed over a stainless steel substrate, to measure the dynamic friction coefficient.
[0060] In one embodiment, the polyimide varnish according to the present invention may have a peel strength after curing of 6 N / cm or more, preferably 6.5 N / cm or more, and more preferably 7 N / cm or more. The peel strength was measured at 90° peel strength at room temperature and 50 mm / sec using a UTM (Instron, model 5564) device, and the measurement was performed using a sample prepared by curing polyimide in the form of a film having a thickness of 25 μm and placing the cured product on a copper foil having a thickness of 36 μm.
[0061] In another aspect of the present invention, there is provided a polyimide coating comprising a cured product of the polyimide varnish.
[0062] In one embodiment, a method for producing the polyimide coating may include the steps of coating a surface of a conductor with a polyimide varnish and imidizing the polyimide varnish coated on the surface of the conductor.
[0063] The conductor may be a copper wire made of copper or a copper alloy, but may also be a conductor made of other metal materials such as a silver wire, or various metal-plated wires such as aluminum or tin-plated wire. The thickness of the conductor and the coating may conform to the KS C3107 standard. The diameter of the conductor may be within a range of 0.3 to 3.2 mm, and the standard coating thickness of the coating (average value of the maximum coating thickness and the minimum coating thickness) may be 21 to 194 μm for type 0, 14 to 169 μm for type 1, and 10 to 31 μm for type 2. The cross-sectional shape of the conductor may be, but is not limited to, a ring wire, a rectangular wire, a hexagonal wire, etc.
[0064] In another aspect of the present invention, there is provided an electric wire comprising the polyimide coating.
[0065] Specifically, the coated electric wire may include a polyimide coating produced by coating the surface of an electric wire with the polyimide varnish and imidizing the polyimide varnish. In one specific example, the coated electric wire may include an electric wire and a coating formed by coating the surface of the electric wire with the polyimide and imidizing the polyimide.
[0066] The present invention also provides an electronic device including the coated electric wire, for example, an electric motor. Effect of the Invention
[0067] The polyimide varnish according to the present invention and the polyimide coating containing the same contain a first additive (boron nitride), a second additive (nanosilica) and a dispersant, and therefore have the effects of improving voltage durability, adhesive strength and thermal conductivity, improving the coefficient of friction and providing excellent dispersibility for the first additive and the second additive.
[0068] In addition, the present invention can improve motor durability and lifespan against partial discharge by improving voltage durability, improve buckling during hairpin processing by improving friction coefficient, and reduce friction during stator insertion to improve defects, thereby improving yield and processability.
[0069] Furthermore, the present invention can be useful in improving motor performance by suppressing the temperature rise of the motor and enabling the rated current to be increased through the improvement of thermal conductivity.
[0070] The present invention also provides improved adhesion and ensures structural and functional reliability even in harsh environments. [Brief description of the drawings]
[0071] [Figure 1] 1 shows SEM images of the surfaces of film-shaped cured polyimide materials prepared by curing polyimide varnishes of Example 1-1, Comparative Example 1-1, and Comparative Example 1-2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0072] In order to facilitate understanding of the present invention, examples are presented. The following examples are provided to facilitate understanding of the present invention, and are not intended to limit the scope of the present invention. EXAMPLES
[0073] <Example> Example 1. Polyimide varnish Example 1-1 A polyamic acid solution was produced by dispersing 99.5-100 mol% of the dianhydride compound pyromellitic dianhydride (PMDA), and 75 mol% of the diamine compounds 4,4'-diaminodiphenyl ether (ODA) and 25 mol% of the p-phenylenediamine (PPD) in 100 mol% N,N'-dimethylacetamide (DMAc), with a target polyimide solid content of 13-25 wt%.
[0074] To the polyamic acid solution, 5 wt% of boron nitride (BN) additive (particle size (D90): 5.4 μm), 0.6 wt% of nanosilica additive (average silica particle size 10 to 20 nm), 0.25 wt% of polyurethane dispersant (amine value 48 mg KOH / g, specific gravity (20°C) 1.05 g / ml), and 0.5 wt% of epoxy silane (OFS-6040) were added to produce a polyimide varnish.
[0075] Example 1-2 A polyimide varnish was produced in the same manner as in Example 1-1, except that 10 wt% of a boron nitride additive and 0.5 wt% of a polyurethane dispersant were added instead of 5 wt% of a boron nitride additive and 0.25 wt% of a polyurethane dispersant in Example 1-1.
[0076] Examples 1-3 A polyimide varnish was produced in the same manner as in Example 1-1, except that 20 wt% of a boron nitride additive and 1 wt% of a polyurethane dispersant were added instead of 5 wt% of a boron nitride additive and 0.25 wt% of a polyurethane dispersant in Example 1-1.
[0077] Comparative Example 1-1 A polyimide varnish was produced in the same manner as in Example 1-1, except that, instead of adding the boron nitride additive, the nanosilica additive, the epoxy-based silane and the polyurethane-based dispersant in Example 1-1, the boron nitride additive, the nanosilica additive, the epoxy-based silane and the polyurethane-based dispersant were not added.
[0078] Comparative Example 1-2 A polyimide varnish was produced in the same manner as in Example 1-1, except that instead of adding 5 wt% boron nitride additive, 0.6 wt% nanosilica additive, and 0.25 wt% polyurethane-based dispersant in Example 1-1, 5 wt% boron nitride additive and 0.25 wt% polyurethane-based dispersant were not added, and 3 wt% nanosilica additive was added.
[0079] The compositions and contents of the polyimide varnishes according to Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 are shown in Table 1. In Table 1, the weight percentages (wt%) of the boron nitride additive, nanosilica additive, and epoxy-based silane indicate the respective contents of the boron nitride additive, nanosilica additive, and epoxy-based silane relative to the solid weight of the polyamic acid varnish, and the weight percentage (wt%) of the dispersant indicates the total content of the dispersant relative to the total weight of the boron nitride additive.
[0080] [Table 1]
[0081] Example 2. Polyimide coating Example 2-1 The polyimide varnish according to Example 1-1 was applied to a copper wire having a diameter of 1 mm in a coating and curing oven, and the process of coating, drying and curing was repeated 20 times or more to produce an electric wire having a polyimide coating having a coating thickness of 100 μm or more.
[0082] Example 2-2 An electric wire including a polyimide coating having a coating thickness of 100 μm or more was produced in the same manner as in Example 2-1, except that the polyimide varnish of Example 1-2 was used instead of the polyimide varnish of Example 1-1 in Example 2-1.
[0083] Example 2-3 An electric wire including a polyimide coating having a coating thickness of 100 μm or more was produced in the same manner as in Example 2-1, except that the polyimide varnish of Example 1-3 was used instead of the polyimide varnish of Example 1-1 in Example 2-1.
[0084] <Experimental Example> Experimental example 1. Physical property evaluation Preparation of cured polyimide varnish in film form for physical property measurement The polyimide varnishes prepared in Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 were rotated at a high speed of 2,000 rpm to remove air bubbles. Next, the degassed polyimide varnish was applied onto a glass substrate (230 mm x 230 mm, thickness: 0.55 mm) using a spin coater. Then, the polyimide varnishes were cured under a nitrogen atmosphere at 110°C (20 minutes) → 150°C (20 minutes) → 200°C (20 minutes) → 300°C (20 minutes) to obtain a polyimide cured product in the form of a film. Here, the polyimide cured product in the form of a film for measuring the voltage durability was prepared to have a thickness of 26±1 μm, and the polyimide cured product in the form of a film for measuring the other physical properties (coefficient of thermal expansion, thermal conductivity, coefficient of friction, and peel strength) was prepared to have a thickness of 20±1 μm.
[0085] FIG. 1 shows SEM images of the surfaces of the polyimide cured films prepared by curing the polyimide varnishes of Example 1-1, Comparative Example 1-1, and Comparative Example 1-2 by the above-mentioned method.
[0086] According to FIG. 1, Comparative Example 1-1 has a clean surface without using any additive, whereas Example 1-1 and Comparative Example 1-2 have additives on the surface, and it can be seen that the dispersant is well dispersed.
[0087] In addition, since Comparative Example 1-2 contains an excess amount of nanosilica, which has a relatively small particle size, it can be confirmed that smaller particles are dispersed in comparison with Example 1-1, which contains both boron nitride and nanosilica.
[0088] (1) Coefficient of thermal expansion (CTE) The polyimide cured films prepared from the polyimide varnishes of Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 were heated from room temperature to 350°C at a heating rate of 10°C / min using a TMA device (Q400) manufactured by TA Corporation, and the gradient in the range of 100 to 250°C was measured. The results are shown in Table 2 below.
[0089] (2) Thermal conductivity The polyimide cured film-shaped materials produced from the polyimide varnishes of Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 were measured for thermal diffusivity in the thickness direction (through-plane) of the cured polyimide varnishes cured under N2 nitrogen gas conditions using a thermal conductivity meter (LFA, NETZSCH, LFA467), and the thermal conductivity was calculated by multiplying the thermal diffusivity measurement value by the density (weight / volume) and specific heat (specific heat measurement value using DSC). The results are shown in Table 2 below.
[0090] (3) Voltage durability The polyimide cured film (thickness: 26±1 μm) produced from the polyimide varnishes of Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 was subjected to a voltage durability test under conditions of AC 1.5 kV, frequency 60 Hz, and upper limit of leakage current 5 mA, using a voltage resistance tester (TSURUGA, 8526). Specifically, the voltage durability was measured by fixing the polyimide to a jig, applying a predetermined voltage, and measuring the time when the leakage current was 5 mA or more. The results are shown in Table 2 below.
[0091] (4) Friction coefficient The friction coefficients of the polyimide cured products in the form of films produced from the polyimide varnishes of Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 were measured using a friction coefficient measuring device (QM110CF, manufactured by QMESYS Co., Ltd.). Specifically, the friction coefficient was measured by fixing one of the polyimide cured products in the form of films to a weight and pulling it at a constant speed on another polyimide cured product in the form of films under the conditions of a load of 200 gf and a speed of 2.5 mm / s, measuring the PI-PI kinetic friction coefficient, and fixing the polyimide cured product to a weight and pulling it at a constant speed on a stainless steel substrate to measure the PI-SUS kinetic friction coefficient. The results are shown in Table 2 below.
[0092] (5) Peel strength The 90° peel strength of the cured polyimide films prepared from the polyimide varnishes of Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 was measured at room temperature at 50 mm / sec using a UTM (Instron, model 5564) and the results are shown in Table 2. Here, the peel strength was measured using a sample prepared by curing the polyimide film having a thickness of 25 μm and placing it on a copper foil (Cu foil) having a thickness of 36 μm.
[0093] The following Table 2 shows the measurement results of the coefficient of thermal expansion (CTE), thermal conductivity, voltage durability, coefficient of friction, and peel strength of the polyimide cured films prepared from the polyimide varnishes of Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2.
[0094] [Table 2]
[0095] From Table 2, it can be seen that the coefficient of thermal expansion (CTE) values of Examples 1-1 to 1-3, which contain the first additive (boron nitride), the second additive (nanosilica) and a dispersant, are smaller than those of Comparative Examples 1-1 and 1-2, and the thermal conductivity is significantly improved compared to Comparative Examples 1-1 and 1-2.
[0096] It can also be seen that the voltage durability and peel strength (adhesive strength) of Examples 1-1 to 1-3 are significantly improved, and the friction coefficient values are relatively small, confirming that the friction coefficient has been improved.
[0097] These results indicate that by appropriately combining dispersants and additives, it is possible to obtain a polyimide varnish that has excellent thermal properties, voltage durability, and adhesive strength, as well as an improved coefficient of friction.
[0098] This specification omits detailed descriptions of contents that can be fully recognized and inferred by a person having ordinary skill in the technical field of the present invention, and various modifications are possible within the scope of the technical ideas and essential configurations of the present invention other than the specific examples described in this specification. Therefore, the present invention can be implemented in a manner different from that specifically described and exemplified in this specification, which is a matter that can be understood by a person having ordinary skill in the technical field of the present invention.
Claims
1. a polyamic acid solution containing a diamine monomer and a dianhydride monomer as polymerization units; a first additive comprising boron nitride; A second additive comprising nanosilica; A dispersant; A polyimide varnish comprising:
2. 2. The polyimide varnish according to claim 1, wherein the first additive is contained in an amount of 1 to 40% by weight based on the solid content weight of the polyimide varnish.
3. 2. The polyimide varnish according to claim 1, wherein the second additive is contained in an amount of 0.01 to 60% by weight based on the solid content weight of the polyimide varnish.
4. The particle size (D90) of the first additive is 1 to 20 μm, 2. The polyimide varnish according to claim 1, wherein the second additive has an average particle size of 1 to 200 nm.
5. 2. The polyimide varnish according to claim 1, wherein the dispersant comprises one or more selected from the group consisting of polyethylene-based dispersants, polyester-based dispersants, polycarboxylate-based dispersants, unsaturated polyamide-based dispersants, polycarboxylate-based dispersants, polyalkyl carboxylate dispersants, polyacrylic-based dispersants, polyethyleneimine-based dispersants, and polyurethane-based dispersants.
6. The polyimide varnish of claim 5 , wherein the dispersant comprises a polyurethane-based dispersant.
7. 2. The polyimide varnish according to claim 1, wherein the dispersant is contained in an amount of 1 to 25% by weight based on the weight of the first additive.
8. The dianhydride monomer is selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylenebis(trimeritic monoester acid anhydride), p-biphenylenebis (trimeritic monoester acid anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl 2. The polyimide varnish according to claim 1, comprising at least one selected from the group consisting of 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride.
9. The diamine monomer is selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP), metaphenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl) 3,3'-diaminodiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diamino diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-amino phenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylsulfide)benzene, 1,3-bis(4-aminophenylsulfide)benzene, 1,4-bis(4-aminophenylsulfide)benzene, 1,3 -bis(3-aminophenylsulfone)benzene, 1,3-bis(4-aminophenylsulfone)benzene, 1,4-bis(4-aminophenylsulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophen bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, The polyimide varnish according to claim 1, comprising at least one member selected from the group consisting of 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.
10. The polyimide varnish according to claim 1 , wherein the polyamic acid solution further comprises an organic solvent.
11. The polyimide varnish according to claim 10, wherein the organic solvent comprises one or more selected from the group consisting of N,N'-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), dimethylsulfoxide (DMSO), diethylacetamide (DEAc), N-ethyl-2-pyrrolidone (NEP), N,N'-diethylformamide (DEF), dimethylpropanamide (DMPA), and γ-butyrolactone (GBL).
12. The polyimide varnish of claim 1 , wherein the polyimide varnish further comprises a silane coupling agent.
13. 2. The polyimide varnish according to claim 1, wherein the polyimide varnish has a solids content of 5 to 40% by weight.
14. 2. The polyimide varnish according to claim 1, wherein the polyimide varnish has a coefficient of thermal expansion (CTE) after curing of 20 to 30 ppm / °C.
15. 2. The polyimide varnish according to claim 1, wherein the thermal conductivity of the polyimide varnish after curing is 0.2 to 0.8 W / mK.
16. 2. The polyimide varnish according to claim 1, wherein after curing of the polyimide varnish, the voltage durability of an insulating material against a predetermined voltage in accordance with IEC-60851-5 is 400 minutes or more.
17. After the polyimide varnish is cured, the coefficient of friction (PI-PI) between cured polyimide varnishes is 0.38 or less; 2. The polyimide varnish according to claim 1, wherein after the polyimide varnish is cured, the coefficient of friction (PI-SUS) between the cured polyimide varnish and a stainless steel substrate is 0.35 or less.
18. 2. The polyimide varnish according to claim 1, wherein the polyimide varnish has a peel strength after curing of 6 N / cm or more.
19. A polyimide coating comprising a cured product of the polyimide varnish according to any one of claims 1 to 18.
20. 20. An electrical wire comprising the polyimide coating of claim 19.
Citation Information
Patent Citations
Heat-conducting polyimide film with dimensional stability at high temperature and preparation method thereof
CN111253601A
High-temperature-resistant polyimide film and preparation method thereof
CN111704798A
Polyimide film with improved thermal conductivity and preparation method thereof
CN114196016A
Corona-resistant polyimide film and preparation method thereof
CN114989466A
Polyimide precursor solution composition containing filler, and polyimide film using same
WO2011001949A1